2011
DOI: 10.1109/led.2011.2167650
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Germanium and Carbon Preamorphization Implant on the Electrical Characteristics of NiSi/Si Contacts With a Presilicide Sulfur Implant

Abstract: This letter reports the demonstration of preamorphization implant (PAI) using germanium (Ge) and carbon (C) and its combination with presilicide sulfur (S) implant for Schottky barrier height (SBH) tuning of nickel silicide (NiSi)-silicon contacts. Ge and C PAI increases the threshold temperature for agglomeration of a NiSi film, thus enhancing its thermal stability. A presilicide S implant and its segregation at metal/semiconductor interface effectively lowers the effective electron SBH Φ n B to 0.18 eV. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It is well known that carbon can effectively enhance the thermal stability of nickel silicide Ni 1-x Si x . [41][42][43][44][45] However, a higher resistivity is also observed for Ni 1-x Si x formed on Si:C where carbon is incorporated in the silicide film. To minimize the carbon-induced R s increase in Ni 1-x Si x , a retrograde carbon profile can be used so that Ni 1-x Si x is formed in a region with lower carbon concentration.…”
Section: Materials Characterization and Discussion For Nickel Silicid...mentioning
confidence: 99%
“…It is well known that carbon can effectively enhance the thermal stability of nickel silicide Ni 1-x Si x . [41][42][43][44][45] However, a higher resistivity is also observed for Ni 1-x Si x formed on Si:C where carbon is incorporated in the silicide film. To minimize the carbon-induced R s increase in Ni 1-x Si x , a retrograde carbon profile can be used so that Ni 1-x Si x is formed in a region with lower carbon concentration.…”
Section: Materials Characterization and Discussion For Nickel Silicid...mentioning
confidence: 99%
“…Se and S implants were performed at energies of 8 and 5 keV, respectively. For S implant, the implant conditions are similar to those in prior reports [1]- [4], [10]- [14]. For Se implant, the energy was selected so that the peak Se concentration is within the top 20 nm of Ge which will later be consumed during NiGe formation.…”
Section: Device Fabricationmentioning
confidence: 99%
“…The electron Schottky barrier height (SBH) of NiSi on n-type silicon (n-Si) is 0.65 eV, and should be lowered to reduce the contact resistance (R C ) and increase the drive current (I Dsat ) in n-channel field-effect transistors [3]- [5]. It has been reported that segregated sulfur (S) atoms at the NiSi/n + Si interface can reduce the effective SBH to ∼0.1 eV [6]- [14]. The S atoms near the interface could act as donor-like traps for narrowing the tunneling width of Schottky barrier [14] or enhance the effective doping concentration under the NiSi/Si interface [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that segregated sulfur (S) atoms at the NiSi/n + Si interface can reduce the effective SBH to ∼0.1 eV [6]- [14]. The S atoms near the interface could act as donor-like traps for narrowing the tunneling width of Schottky barrier [14] or enhance the effective doping concentration under the NiSi/Si interface [15]. Another important technique used in advanced contact formation is the preamorphization implant (PAI) before silicidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation